An Analysis of Selling Price Determination Practices from Imam Al-Ghazali's Islamic Economic Perspective A Case Study of the Jeges Photocopy Business - Pitriani; Zaenal Abidin; Siti Fatimah; Najwa Aulia Habibah; Anita Schenk (Zabags International Journal of Economy, 2026)
This study addresses the urgency of fair pricing practices in Islamic economics, particularly through the perspective of Imam Al-Ghazali, who emphasized the balance between sellers’ and buyers’ interests and the avoidance of exploitative practices. The primary objective of this research is to examine the pricing strategies applied by Fotocopy Jeges in Kelurahan Rano and to evaluate their alignment with Al-Ghazali’s principles of price fairness, honesty, and reasonable profit. Employing a qualitative descriptive approach, the study collected primary data through interviews and observations with the owner, employees, and regular customers, complemented by secondary data from relevant academic literature. The findings reveal that pricing decisions are primarily based on operational costs, service quality, and consumer perceptions, with efforts to maintain transparency and ensure equitable profit margins. These results highlight that the pricing practices at Fotocopy Jeges reflect the ethical and justice-oriented values of Islamic business principles, although challenges remain in consistently ensuring transparency across certain services. The contribution of this study lies in extending the application of Al-Ghazali’s concept of fair pricing to the micro-service sector, enriching the body of literature on Islamic economics, and offering practical implications for microenterprise practitioners and policymakers in formulating socially oriented pricing strategies.